Hubungan Komitmen dan Penyesuaian Perkawinan dengan Kepuasan Perkawinan pada Istri Anggota Batalyon Paskhas 467 TNI AU yang Menjalani Long Distance Marriage - Aurina Anindya Nawang Safitri; Hardjono; Fadjri Kirana Anggarani (Jurnal Ilmiah Psikologi MIND SET, 2020)
Marital satisfaction is one of the important things in supporting the happiness of a partner. The emergence of conflict in marriage is normal for couples, but can be more complicated for couples who undergo long distance marriage (LDM) because they are unable to actualize the needs, hopes, and desires that affect satisfaction in marriage. Marital commitments and marital adjustments can increase marital satisfaction. This study aims to determine the correlation between marital commitment and marital adjustment with marital satisfaction on wives who undergo long distance marriage at Halim Perdanakusuma. This study uses a non random purposive sampling involving 72 wives of the Air Force soldiers in Battalion Paskhas 467 Halim Perdanakusuma as a sample and uses a marital satisfaction scale, a marital commitment scale, and a marital adjustment scale as an instrument . The results of multiple regression analysis showed a strong positive significant correlation between marital commitment and marital adjustment with marital satisfaction for wives undergoing LDM. Significantly positive correlation between marital commitment and marital satisfaction on wives undergoing LDM.. Significantly positive correlation between marital adjustment and marital satisfaction among wives undergoing LDM. The conclusion of this study is the higher marital commitment and marital adjustment to wives undergoing long distance marriage, the higher marital satisfaction is felt.